Preservation of Cultural Heritage in an Ethnic Minority Using Internet of Things and Smart Karaoke - Ochoa, Alberto (IGI Global, 2020)
This research describes an intelligent tool based on a karaoke system to represent the linguistic resources related to a social network for music and songs associated with a cultural bulwark: Otomí (a language spoken in México). This system employs a representation of the Dublin Core metadata standard for document description, composed by XML standard to describe profiles and provide recommendations to a group of persons associated with this social network. The novel idea of this research is the analysis (with an improved methodology) of each search to provide a recommendation based on petitions of each user in this social network, reducing the human efforts spent on the generation of a specific profile. In addition, this chapter presents and discusses some experiments to corroborate the impact of this research, based on quantitative and qualitative evaluations. This chapter introduces an innovative idea of how to help this type of ethnic group.